Sengketa Tanah Antara Masyarakat dengan Pemerintah (Studi Kasus: Pembangunan Dinas PUPR di Jawa Timur) - Fitrotul Maulidah; Humaida Maulina; Lala Alfiana; Muhamad Niko Dardiri; Hany Nurpratiwi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The rise of land disputes in Indonesia does not only occur between families and neighbors, but also between communities and the government. It is unfortunate, considering that the conflicts that occur are also caused by unequal goals. Therefore, the conflict over land disputes between the community and the government is the main discussion in this article. This study aims to find out how land dispute conflicts occur and how to resolve these land dispute conflicts. To complete this article, the literature study method through collecting research data sourced from books, journals and previous articles is used, because it has compatibility in data collection. Based on this research, it can be concluded that the land dispute conflicts that occur are motivated by the complexity of land acquisition and the community feels they have no advantage over land acquisition.